The relationship between authentic leadership and employee's job performance at Wisma Persekutuan Kuantan, Pahang / Nazatul Shafina Ideris Shah - Ideris Shah, Nazatul Shafina (Faculty of Business and Management, 2018)
The purpose of this study is to identify the factor of authentic leadership affecting the employee's job performance. The study has been conducted at Wisma Persekutuan Kuantan, Pahang. The number of employees in Wisma Persekutuan Kuantan is 420 people. The researcher selected 126 people as respondents from all departments, namely 12 departments. 126 questionnaires has been distributed to the employees within one week by using simple random sampling technique. The researcher described authentic leadership as the individual who have natural attitudes that make them have competencies to lead the others. The authentic leaders influence employees to constantly improve their work and performance outcomes. And also, they can make people confident to listen to their lead. This study examining the authentic leadership with four variables which are self-awareness, relational transparency, internalized moral perspective and balanced processing influence the job performance of employees. Besides, the type of research design that used for this study is non-experimental research and research design that have been choose is correlational. The results provide evidence that there is a positive significant relationship between authentic leadership and employee's job performance. Employee's job performance positively affected to employee's productivity. The authentic leaders influence employees to constantly improve their work and performance outcomes by enhancing engagement in and commitment to work. Other than that, when provide a training to employees, praise and reward the employees and also assessing the work environment in the organization, the employees will recognizes their organization interest in them and in tum they will apply their best efforts to achieve organizational goals and show high performance on job.